Review of Control Strategies for DC Nano-Grid - Fan, Hong; Yu, Weinan; Xia, Shiwei (Frontiers in Energy Research, 2021)
As an emerging energy management technology, the DC nano-grid coordinates renewable energy sources output through demand-side management which would provide more options and flexibility for the dispatch of smart buildings and communities with high reliability and efficiency. In this context, this article has analyzed the structure and components of the DC nano-grid. The role and components in DC nano-grid are reviewed in this article. Then the crucial control technologies for the DC nano-grid in recent years are investigated from two aspects: local control and coordinated control, which contains control schemes such as voltage/current control technology, power-sharing technology and cooperative control technology. Different control strategies at various levels are compared and their application scenarios, advantages and disadvantages are also analyzed. The current research progress and challenges are summarized at the end of this article.